Impact of the first wave of COVID-19 on Crohn’s disease after the end of “zero-COVID” policy in China - Hu, Wen; Li, Xiao; Yan, Zelin; Wang, Qiuzhi; Luo, Jiakai; Yu, Qiao; Li, Shuyan; Lu, Shiyuan; Roozbahani, Atiyeh; Ghoushi, Ehsan; Chen, Yan; Li, Jun (Frontiers in Public Health, 2023)
Background The incidence and severity of coronavirus disease 2019 (COVID-19) among Crohn’s disease (CD) patients are unknown in China. This study aimed to clarify the clinical courses and outcomes of CD patients in the first COVID-19 wave after the end of “zero-COVID” policy in China. Methods Clinical characteristics, including vaccination doses and medications of 880 CD patients from a prospective cohort were collected for analysis. Results Of the enrolled patients (n = 880) who underwent nucleic acid or antigen testing for COVID-19 from Dec 7, 2022, to Jan 7, 2023, 779 (88.5%) were infected with COVID-19. Among the infected patients, 755 (96.9%) were mild, 14 (1.8%) were moderate, one patient with leukemia died of cerebral hemorrhage (mortality, 0.1%) and only 9 (1.2%) were asymptomatic. Fever, cough, headache and appetite loss were the most frequently observed symptoms in general, respiratory, neurological and gastrointestinal manifestations, respectively. The age and disease duration were significantly higher (40/32, 5.6/3.6, all p < 0.05) in moderate patients than those in mild patients. All other clinical characteristics, including CD activity and medication exposure, showed no significant differences between the above two groups. Furthermore, no significant difference in vaccination or comorbidities was observed between the two groups. Conclusion Most CD patients contracted the Omicron infection and experienced mild disease courses in the first COVID-19 wave attack after China ended the “zero-COVID” policy irrespective of vaccination dose or comorbidities.